Effect of Fe-doping on the structural, optical and magnetic properties of ZnO nanostructures synthesised by co-precipitation method. Issue 1 (January 2016) - Fabbiyola, S.; Kennedy, L. John; Ratnaji, T.; Vijaya, J. Judith; Aruldoss, Udaya; Bououdina, M.
Abstract: Nanoparticles of Zn1− x Fe x O (0≤ x ≤0.2) were prepared by co-precipitation method followed by drying at 200 °C. Tween-80, a non-ionic surfactant, not reported in earlier studies was used during preparation process. X-ray diffraction analysis showed the formation of wurtzite ZnO phase nanostructures. The Rietveld analysis confirmed the formation of hexagonal wurtzite structure for all dopant levels without any impurity. Morphological observations using scanning electron microscopy show the formation of nanoparticles with remarkable morphologies. Photoluminescence spectra revealed emission bands in both UV and visible regions due to the defect centres acting as trap levels. Optical studies carried out by diffuse reflectance spectroscopy (DRS) indicated a decrease in the value of the band gap with increasing Fe doping concentration. The elemental composition of Zn, Fe and O quantitatively obtained from EDAX analysis confirmed the purity of the as-prepared nanopowders and that the chemical composition is close to the starting stoichiometries. Magnetization–Field ( M – H ) hysteresis curves revealed the appearance of ferromagnetic behaviour, where the magnetic characteristics such as coercivity and saturation magnetization values, were found to be sensitive to Fe doping level.